Penggunaan E-Learning sebagai Media Penunjang Mutu Pembelajaran di Prodi Pendidikan Ekonomi STKIP PGRI Lumajang - Fidyah Jayatri; Triwilujeng Ayuningtyas; Cindy Dwi Andriani (Proceedings of The ICECRS, 2019)
Digitalization is developing rapidly in the community, but not all levels of society can use technology properly including students. So that it needs an active role of universities in directing students to be more effective in using technology as a learning support facility. The purpose of the study was to determine the extent to which the use of e-learning in the Economic Education Study Program of STKIP PGRI Lumajang can spur student academic activities on an ongoing basis so as to improve the quality of learning. This type of research uses a qualitative phenomenological approach. The research method uses in-depth interviews, observations and questionnaires. Found the results of the first study, most of the students of Economic Education Study Program were able to use e-learning well. Second, the intensity of e-learning media usage is not routinely fully used by students because not all subjects are given through e-learning media. Finally, the use of e-learning media provides an attraction to encourage students to be more active, more effective in understanding the material, more efficient in terms of time and cost. The main problem that arises is the unstable internet network connectivity because most student residences are in locations that are difficult to reach with a strong internet network so they have to struggle more to be able to access e-learning.